AN EMPIRICAL MODEL FOR EXPLORING AI IN GOVERNMENT: PUTTING SOCIO-TECHNOLOGICAL SYSTEMS PERSPECTIVES INTO USE - Arslan, Ayse Kok (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2021)
This study explores the evolution of global AI dynamics by discussing its role in government with a focus on aspects of development and governance of social and technological systems (STS). This document reports three research questions, including the extent of the analysis: (1) theories regarding the concept of AI in the public sector; (2) expectations regarding the development of AI in the public sector; and, (3) the challenges and opportunities of AI in the public sector. This experimental study provides an experimental framework for a comprehensive approach to measuring the magnitude of AI policy that allows for the methods of evaluating different governance practices and policy priorities in different countries. The study sheds light onto areas of policy that have the potential to implement AI programs and strategies; administrative functions open to the acceptance of AI applications and strategies; and the challenges / risks that community managers may face in defining AI policies and projects in the public sector including how to deal with cyber-troops.